Environmental dynamics recorded at Dupljaja loess section (Southeastern Carpathian Basin, Northern Serbia) - Marković, Slobodan B.; Hao, Qingzhen; Ludwig, Patrick; Zeeden, Christian; Perić, Zoran ; 0000-0003-0116-8895; Mihailović, Dušan; Radović, Predrag; Roksandić, Mirjana; Lindal, Joshua; Krsmanović, Petar; Baykal, Yunus; Vandenberghe, Jef; et al. (INTERNATIONAL CONFERENCE Geospatial and Environmental Dynamics – LAMINATION, Novi Sad, Serbia, 2025-11-15 - 2025-11-16, 2025)
Dupljaja loess-palaeosol sequence in southeasternmost sector of the Banat Loess Plateau (Serbia), situated in the southeastern Carpathian (Middle Danube) Basin, is important for understanding the evolution of the Last Glacial climate and southeastern Carpathian as a potential corridor for human migration throughout Europe. The Dupljaja loess-palaeosol sequence in the southeasternmost sector of the Banat Loess Plateau, Serbia, is of significant paleoenvironmental importance. Situated within the southeastern Carpathian (Middle Danube) Basin, it provides valuable insights into the climatic evolution during the last glacial period and highlights the southeastern Carpathians as a potential migration corridor for early humans across Europe. The stratigraphic pattern of the Dupljaja section from the Holocene to the Last Glacial period mirrors analogous profiles in the northern Serbia, with the robust support based on luminescence dating and the correlation of magnetic record with the Marine Oxygen Isotope stratigraphy. Importantly, the grain size data from the section provides crucial insight into egional dust accumulation dynamics on the southeastern Banat Loess Plateau. Three distinct depositional modes are identified: two finer modes were dominant in the Holocene and late Last Glacial intervals, whereas a coarser mode prevailed in the Marine Isotope Stage (MIS) 3 interval. To better understand these variations in grain size records, we have undertaken a comparative analysis of regional palaeoclimate model data between the Last Glacial Maximum (LGM) and typical Greenland Stadial and Interstadial conditions. Model results indicate slightly drier regional climate conditions during the LGM than during stadial, while granulometry data suggests that the deposition of coarser loess during MIS 3 is related to drier conditions in the local source area (the Danube River alluvial plain), resulting in coarser material available for aeolian action. We propose that the drier hydroclimate of the Danube Palaeolithic corridor associated with steppic and more seasonal environmental conditions between 53–37 ka may have facilitated migrations of anatomically modern humans from southwest Asia into Europe.